2000
DOI: 10.1182/blood.v96.13.4328
|View full text |Cite
|
Sign up to set email alerts
|

BAL is a novel risk-related gene in diffuse large B-cell lymphomas that enhances cellular migration

Abstract: Clinical risk factor models such as the International Prognostic Index are used to identify diffuse large B-cell lymphoma (DLB-CL) patients with different risks of death from their diseases. To elucidate the molecular bases for these observed clinical differences in outcome, differential display was used to identify a novel gene, termed BAL (B-aggressivelymphoma), which is expressed at significantly higher levels in fatal high-risk DLB-CLs than in cured low-risk tumors. The major BAL complementary DNA encodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(65 citation statements)
references
References 30 publications
0
64
0
1
Order By: Relevance
“…It is now well established that various members of the macro domain family are overexpressed in a range of human tumors [73][74][75][76][77][78][79][80]. Generally, MACROD1 appears to be the family member most widely overexpressed in human cancers, with high levels of expression observed in endometrial carcinoma, gastric carcinoma, colorectal carcinoma, and breast carcinoma [74][75][76][77][78].…”
Section: Macro Domains In Cancer and Degenerative Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is now well established that various members of the macro domain family are overexpressed in a range of human tumors [73][74][75][76][77][78][79][80]. Generally, MACROD1 appears to be the family member most widely overexpressed in human cancers, with high levels of expression observed in endometrial carcinoma, gastric carcinoma, colorectal carcinoma, and breast carcinoma [74][75][76][77][78].…”
Section: Macro Domains In Cancer and Degenerative Diseasesmentioning
confidence: 99%
“…Important molecular marker correlations are also now beginning to be drawn. Clinical research has indicated that the expression level of some of macro domain proteins in carcinoma is significantly higher than that in matched normal tissues and is correlated significantly with shortened survival in patients with cancer [76][77][78][79]81]. In addition, macro domain proteins could become useful biomarkers to predict the risk of recurrence of some tumors.…”
Section: Macro Domains In Cancer and Degenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…It usually exists on its own as a small protein, but the human genome also contains open reading frames in which this domain is repeated. A gene termed BAL, which contains a duplicated nsP3-like domain, is a highly expressed risk factor in certain aggressive lymphomas (140). The conservation between viral and cellular homologs is unusually high for an RNA virus protein, reaching up to 35-40% sequence identity (139).…”
Section: A Sequence Conservationmentioning
confidence: 99%
“…12 Three human genes encode the B-aggressive lymphoma (BAL) family of transcription factors. [13][14][15] BAL proteins include two or three tandem macro domains followed by a poly (ADP-ribose) polymerase (PARP) domain, reinforcing the link of the macro family with ADP-ribose derivatives. The final three human macro domain proteins are poorly understood.…”
Section: Introductionmentioning
confidence: 99%